Development of Multimedia-Based Edutainment for Learning About Animals and Plants: A Case Study at PAUD Bunda Pratiwi - Sanriomi Sintaro (PT. Tech Cart Press, 2025)
This study examines the need for interactive multimedia-based learning to help young children, especially in preschool education, recognize animals and plants through information technology. Traditionally, teaching methods have relied on blackboards, books, and environmental exposure, with some educators incorporating interactive videos from platforms like YouTube. However, with rapid technological advancements, computer-based learning using interactive multimedia presents a more engaging alternative. Interactive multimedia integrates visual programming, sound, text, and images, creating a more dynamic and comfortable learning experience. Its implementation in education is expected to boost children’s enthusiasm and comprehension by making lessons more visually appealing and easier to understand. The research aimed to develop an application that enhances learning through multimedia technology and assess its effectiveness in addressing educational challenges. To evaluate the application's impact, scenario-based tasks were assigned to respondents, followed by a System Usability Scale (SUS) questionnaire to measure user satisfaction. The results showed an average SUS score of 91.92, placing it in the